Quality of public health insurance and individuals' consumption structure upgrades: Evidence from China - Pengfei Zhang; Jinghua Gao (Health Economics Review, 2021)
Background: The aim of this study was to investigate the relationship between the quality of public health insurance and individuals'consumption structure upgrades in China. Methods: This study was conducted using data from a population of 6430 Chinese individuals aged 18 to 70 y from the 2017 Chinese Social Survey. We used multiple linear regression models and the two-stage least-squares model to explore the impact and heterogeneity of the quality of public health insurance on individuals' consumption structure upgrades. Furthermore, we performed structural equation modelling to clarify the mediation effects of the impact. Results: The quality of public health insurance was significantly correlated with individuals'consumption structure upgrades (Ø= 0.368, SD = 0.084), and the impact of the quality of public health insurance on individuals'hedonic consumption in urban regions was significantly higher than that in rural regions (Ø= 0.499, SD = 0.218). Furthermore, the quality of public health insurance could promote upgrades to individuals'consumption structure by reducing the burden of medical expenses and stabilizing or increasing individuals'expectations regarding the future economic level. Conclusion: The results indicated that developing countries should implement additional measures to enhance the quality of public health insurance, which would not only help protect the health of individuals but also stimulate individuals'consumption to achieve rapid economic growth.
Keywords: 330; Public health insurance; Quality; Consumption structure upgrade